Regulation of the Autonomic Nervous System on Intestine - Duan, Hongyi; Cai, Xueqin; Luan, Yingying; Yang, Shuo; Yang, Juan; Dong, Hui; Zeng, Huihong; Shao, Lijian (Frontiers in Physiology, 2021)
Intestine is composed of various types of cells including absorptive epithelial cells, goblet cells, endocrine cells, Paneth cells, immunological cells and so on, which play digestion, absorption, neuroendocrine, immunological function. Intestine is innervated with extrinsic autonomic nerves and intrinsic enteric nerves. The neurotransmitters and counterpart receptors are widely distributed in the different intestinal cells. Intestinal autonomic nerve system includes sympathetic and parasympathetic nervous systems, which regulate cellular proliferation and function in intestine under physiological and pathophysiological conditions. Presently, distribution and functional characteristics of autonomic nervous system in intestine were reviewed. How autonomic nervous system regulates intestinal cell proliferation was discussed. Function of autonomic nervous system on intestinal diseases was extensively reviewed. It might be helpful to properly manipulate autonomic nervous system during treating different intestinal diseases.